UPAYA PENYELESAIAN BANK UNTUK MENGATASI PENYIMPANGAN BAIK YANG DILAKUKAN OLEH PENERBIT MAUPUN PEMEGANG KARTU KREDIT - Zakaria Zakaria (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Irregularities in the use of credit cards that can be distinguished by behavior, namely: Deviations made by the card holder; Deviations made by merchants.Bank efforts to overcome various deviations either by card holder or merchant, among others are: To overcome the use of credit cards that exceed the credit limit made with transactions under the floor limit, the Issuer (bank) for the first time will give a warning to card holders not to use credit cards that exceed the credit limit, even if the card holders have sufficient funds. If the violation of the credit limit is exercised even if the warning has been given three times, the issuer (bank) may cancel the card and put it in the blacklist and the card holder shall be obliged to pay off all outstanding obligations; To overcome the frequent late card holder in paying his account bills, Issuer (bank) will give a warning to card holder.dengan give a penalty for late paying the account; Efforts or steps taken by the bank to tackle the actions of the merchant to make a higher price on the card holder are: The Bank for the first time will give warning to the merchant not to commit the infringing act. If the transaction deal is still committed by the merchant, then the issuer (bank) will further impose sanctions. The last attempt by the issuer (bank) is the cancellation / termination of the agreement; Efforts or steps taken by banks to solve merchant actions to duplicate sales draft or fictitious transaction are: Bank will give warning to the merchant and accompanied by sanction that will refuse payment of fictitious transaction if the fictitious transaction bill has not been paid by issuer. If the fictitious transaction bill has already been paid by the issuer and signed in the card holder bill account whose name and credit card number is used in the fictitious transaction, then the issuer (bank) will deduct / refund the invoice already paid by the issuer. If the invoice or fictitious duplication is repeated many times, it will be unilaterally terminated by the issuer (bank). In addition to the first way, the issuer (bank) can file a lawsuit to the District Court.Forms of legal protection against the parties in issuing credit cards include: Forms of legal protection for card holder in case of loss of credit card. By having a credit card by the card holder, then the card holder has the right to conduct transactions with the merchant. In the use of credit cards is not closed the possibility of credit card is lost